2018
DOI: 10.1007/s13524-018-0688-1
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Weights for Analyses of Couple Data: Example of the Demographic and Health Surveys

Abstract: In some surveys, women and men are interviewed separately in selected households, allowing matching of partner information and analyses of couples. Although individual sampling weights exist for men and women, sampling weights specific for couples are rarely derived. We present a method of estimating appropriate weights for couples that extends methods currently used in the Demographic and Health Surveys (DHS) for individual weights. To see how results vary, we analyze 1912 estimates (means; proportions; linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Actually, weights for women or men include response rates for both single and in-union individuals grouped together so are not really appropriate for couples since response rates vary by union status. However, in comparison to results with a proposed couple weight, men's and women's weights both typically gave results with a similar and small level of bias(Becker and Kalamar 2018).Studies in Family Planning 49(2)June 2018…”
mentioning
confidence: 92%
“…Actually, weights for women or men include response rates for both single and in-union individuals grouped together so are not really appropriate for couples since response rates vary by union status. However, in comparison to results with a proposed couple weight, men's and women's weights both typically gave results with a similar and small level of bias(Becker and Kalamar 2018).Studies in Family Planning 49(2)June 2018…”
mentioning
confidence: 92%
“…In contrast, the share of other modern contraceptives -which include diaphragm, foam, and jelly -which was already low in 2005-06 decreased further during the inter-survey period. In this context, it is necessary to note that the percentage increase in the use of pills, injectables, and condoms between 2005-06 and 2015-16 was 32.3%, 79.2%, and 7.7%, respectively, whereas the use of IUD decreased by 11.8% during the same period (data not shown here) [36,37].…”
Section: Resultsmentioning
confidence: 98%
“…This issue cannot be bypassed by applying women's or men's sampling weights as doing so creates a significant bias in the results. The solution is to develop sampling weights for the couples to make the results representative [37]. Accordingly, normalized couple sampling weights were generated for this study based on the methodology suggested by Becker & Kalamar in 2018 [37].…”
Section: Generating Sampling Weights For Couplesmentioning
confidence: 99%
See 1 more Smart Citation
“…All descriptive and multivariable analyses are weighted using the men's weights based on the recommendation by the DHS to use men's weights when couple-level weights are not available. In an earlier paper, Becker and Kalamar (2018) demonstrate a strategy to create couple-level weights with DHS data; however, the required information to create these weights is not typically included as part of the DHS data sets. All analyses adjust the standard errors for the clustered sampling design in the DHS surveys.…”
Section: Discussionmentioning
confidence: 99%